Approach to environmental education in public schools in the municipality of União – Piauí, Brazil in the context of the Covid-19 pandemic (Research, Society and Development, 2024)
The school becomes an ideal environment for carrying out theoretical-practical activities in order to form critical and ecologically aware generations. Given this statement, Environmental Education enables the construction of the individual's ecological thinking with the perspective of changing attitudes and practices in relation to environmental conservation. This article aims to evaluate the Environmental Education actions implemented in schools in the municipal education network of União, Piauí, Brazil, during the Covid-19 pandemic. The actions developed in municipal schools follow the notice of the State Secretariat for the Environment and Water Resources of Piauí, for qualification and postulation regarding the certification of the Environmental Seal in 2021. The study had a descriptive/qualitative approach through a research of the legal instruments sanctioned by the Municipal Executive Branch, available on the official website of the Municipal Government of União-PI, in addition to consultations in the scientific literature, which deals with specific legislation on Ecological ICMS, and official information from the Municipal Department of Education. A schedule was prepared with a description of the following actions carried out in 2021: continuing training course for teachers in the municipal education network, focusing on Environmental Education; development of interdisciplinary projects, involving socio-environmental themes; holding Municipal Environment Week; and the distribution and planting of native seedlings. The actions followed the Covid-19 protocol. It is expected that the educational activities have contributed to the construction of knowledge and changes in students' behavior and raised awareness about environmental conservation.